The Causal Relationship of Strategic Management Accounting Practices, Intellectual Capital Development and Firm Success - Hannimitkulchai, Kwanchanok (University of the Thai Chamber of Commerce Journal Humanities and Social Sciences, 2021)
This research aims to investigate the causal relationships of strategic management accounting practices on intellectual capital development and firm success. These relationships were tested with data from 298 information and communication technology firms in Thailand. Data were collected via questionnaires, and Structural Equation Modeling (SEM) was used to analyze the data. The results showed that the causal relationship model fit to the empirical data was at the acceptable level (χ2 = 116.086, p-value = 0.008, CFI = 0.989, IFI = 0.989, GFI = 0.951, RMSEA = 0.037). The results also indicated that strategic management accounting practices had positive direct effects on intellectual capital development, which had a positive direct effect on firm success (b = 0.664, 0.298, respectively). Moreover, it showed that strategic management accounting practiceshad an indirect effect on firm success through intellectual capital development (b = 0.226). Thus,firms need to be aware of implementing five SMAPs: costing, performance measurement, strategic decision-making, competitor accounting, and customer accounting to identify and understand how intellectual capital works, and to measure and evaluate intellectual capital in diverse dimensions in order to provide information needed for intellectual capital development which play a vital role in maximizing value creation and result in good performance.